2021
DOI: 10.1016/j.chemosphere.2020.127917
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury displays pro-adipogenic properties in rainbow trout preadipocytes

Abstract: h i g h l i g h t s MeHg induced a dose-dependent accumulation of neutral lipids in preadipocytes. Accumulation of lipids persisted beyond the cellular exposure to MeHg. MeHg increased n-3 PUFA levels in lipid droplets and dropped AA levels in membranes. Expression of adipocyte-and lipid-specific genes was modulated by MeHg. Total mercury accumulated in cells was released when MeHg exposure stopped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…We are unaware of other studies of the effects of mercury on PPAR -γ (or other PPARs) in birds, but effects in other taxa have been inconsistent. For example, mercury increased PPAR -γ expression in nematodes 26 , rat adipocytes 65 , and fish brain cells 66 , while it decreased it in mouse fibroblasts and adipocytes 23 , 67 , and had no effect in fish preadipocytes 53 . Interestingly, Corder et al 68 found liver expression of PPAR -γ and target genes for FAT/CD36, FABPpm, and cytosolic FABP in migratory gray catbirds ( Dumetella carolinensis ) to remain similar across the annual cycle, indicating increased expression of PPAR -γ and fatty acid transporters may not be needed for the liver to meet the metabolic demands of migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are unaware of other studies of the effects of mercury on PPAR -γ (or other PPARs) in birds, but effects in other taxa have been inconsistent. For example, mercury increased PPAR -γ expression in nematodes 26 , rat adipocytes 65 , and fish brain cells 66 , while it decreased it in mouse fibroblasts and adipocytes 23 , 67 , and had no effect in fish preadipocytes 53 . Interestingly, Corder et al 68 found liver expression of PPAR -γ and target genes for FAT/CD36, FABPpm, and cytosolic FABP in migratory gray catbirds ( Dumetella carolinensis ) to remain similar across the annual cycle, indicating increased expression of PPAR -γ and fatty acid transporters may not be needed for the liver to meet the metabolic demands of migration.…”
Section: Discussionmentioning
confidence: 99%
“…We are unaware of any prior studies of the effects of mercury on fatty acid transporters in birds, but fatty acid transporters in other taxa have shown mixed responses. For example, exposure of fish to MeHg increased expression of cytosolic FABP in preadipocytes 53 and muscles 54 , while it decreased FABPpm expression in preadipocytes 53 , hepatocytes 55 , and kidney cells 45 . FAT/CD36 expression was reduced in adipocytes of mice exposed to mercury chloride 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of MeHg on driving adipocyte differentiation seems to be conserved across species. In primary pre-adipocytes from rainbow trout ( Oncorhynchus mykiss ) exposed to MeHg for 6 days, there was an accumulation of neutral lipids as well as the upregulation of genes that are markers of mature adipocytes, including perilipin 2, apolipoprotein Eb, fatty acid synthase, and fatty acid binding protein [ 237 ].…”
Section: Introductionmentioning
confidence: 99%